2017
DOI: 10.1002/hon.2437_90
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Strategies and Outcomes in Diffuse Large B‐cell Lymphoma of the Elderly: A Danish Population‐based Cohort Study of 1,011 Patients

Abstract: from CLL11 (n = 132), CLL1 (n = 3), CLL5 (n = 1), CLL7 (n = 3), CLL8(n = 2), CLL9 (n = 9), and CLL10 (n = 2). Median age was 82 years (range [80][81][82][83][84][85][86][87][88][89][90]. Concomitant diseases were present in 99% of the pts and median cumulative illness rating scale (CIRS) score was 8 (0-18).Median creatinine clearance was 46 mL/min (range 17-99 mL/min).Distribution of CLL-IPI risk groups was as follows: 6% low, 19% intermediate, 61% high, and 14% very high. Most pts had Binet stage B (36%) or C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…A further contribution to this observation may be the increasing dose intensity given to elderly patients with DLBCL in more recent years. We recently showed that anthracycline containing therapy was administered in 71% of patients above 74 years, in the period from 2008 to 2012, compared to only 57% between 2003 and 2007 37 . The more frequent use of anthracyclines in patients above 74 years seen in recent years probably reflects a combination of factors, such as a more fit elderly population, better supportive strategies, and a consequent shift toward a more curatively intended approach in the elderly.…”
Section: Discussionsupporting
confidence: 90%
“…A further contribution to this observation may be the increasing dose intensity given to elderly patients with DLBCL in more recent years. We recently showed that anthracycline containing therapy was administered in 71% of patients above 74 years, in the period from 2008 to 2012, compared to only 57% between 2003 and 2007 37 . The more frequent use of anthracyclines in patients above 74 years seen in recent years probably reflects a combination of factors, such as a more fit elderly population, better supportive strategies, and a consequent shift toward a more curatively intended approach in the elderly.…”
Section: Discussionsupporting
confidence: 90%
“…At present, the incidence of NHL demonstrates a significant upward trend in different stages of age [1]. Certain patients with NHL can achieve complete remission after a short duration of chemotherapy under the R-CHOP regimen [2]. Unfortunately, about 50% of such patients will relapse, and the 3-year overall survival rate after recurrence is about 30% [3].…”
Section: Introductionmentioning
confidence: 99%